Territorial rule in Colombia and the transformation of the Llanos Orientales - Rausch, Jane M., 1940- (University Press of Florida, 2013)
An examination of the Llanos Orientales of Colombia (an area that, up to the 1980s, could still be considered frontier) and the effects of the discovery of petroleum in the region - and the rapid growth that ensued.